Eksistensi Badan Pertanahan Aceh sebagai Perangkat Daerah di Aceh dalam Aspek Kepastian Hukum Bidang Pertanahan - Zaki 'Ulya (The Constitutional Court of the Republic of Indonesia, 2015)
Under the provisions of Article 253 of Law No. 11 Year 2006 regarding Aceh Government insists on the transitional status of the Regional Office of the National Land Agency of Aceh and District Land Office / City into the device unit area of Aceh and district / city, which is limited to the budget end of 2008. However, the status of the new transition can be completed in the year 2015 with the issuance of Presidential Decree No. 23 Year 2015 on the transfer of the Regional Office of the National Land Agency of Aceh and District Land Office / City Land Agency Become Aceh and Aceh Land Office Regency / City. The problems that arise as a result of the enactment of legislation that is related to the authority of the President of the Regional Office of the National Land Agency of Aceh are still centralized, resulting in disharmony between the legal provisions of Law No. 11 of 2006 by Presidential Decree No. 23 Year 2015. The purpose of this paper is intended to examine the form of disharmony legal provisions of Article 253 of Law No. 11 Year 2006, which refers to Memorendum of Understanding (MoU). And, examine the impact of the authority of the National Land Agency of Aceh on the enforceability of Presidential Decree No. 23 Year 2015.